Zobowiązania agentów morskich i agentów handlowych w dziełach szkockich pisarzy instytucjonalnych - Szymura, Mateusz (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
In this work the development of the Scottish institutions of maritime and mercantile agency from the second half of the 17th to the second half of the 18th century in Scottish law was presented. It was a period of transition between an independent civilian-based Scottish legal system and the earliest stage of development of a hybrid legal system which Scotland has today.The text consists of three distinct parts. The first one describes Scottish law as a mixed legal system and shows the important role of institutional writings as the source of law. The second focuses on the relation between maritime agent and his principal and their liability to agent’s contractor. The last part describes the institution of mercantile agent and the similarities and differences in comparison to maritime agency.
Keywords: agency; institor; exercitor; mixed jurisdictions; Scotland; institutional writers; James Darymple; Andrew MacDougall; John Erskine